Economic Factors Influencing the Probability of Adjustments in Nepal’s Exchange Rate Policy with the Indian Currency - Maskay, Nephil Matangi (NRB Economic Review, 2001)
A binomial probit analysis, using the monetary model of exchange rate determination, is applied to understand economic influences on the probability for adjustment in Nepal’s exchange rate policy with the Indian Currency during the period of 1976 - 1998. Empirical results suggest that both relative Nepalese to Indian money and output growth does not have significant effects on probability of exchange rate change but that the relative interest rate growth does. Additionally, the movement of relative interest rate growth variable of Nepal and India is seen to signal changes in real, versus nominal as put forward in the monetary model, rates of return whose divergence increases the probability of appreciation of the Nepalese Currency vis-à-vis the Indian Currency.